Sintesis dan Aplikasi Komposit ZnO-Karbon Aktif untuk Fotodegradasi Direct Blue 3R serta Fotoreduksi Ion Logam Pb2+ dan Cd2+ Secara Simultan - Muchit, Moch Ali (Chem Info Journal, 2013)
Synthesis and aplication of ZnO-active carbon composite for direct blue 3R photodegradation and Pb2+ and Cd2+ ions photoreduction. Have been conducted for characterisation of synthesid by XRD obtained ZnO (wurzite) with crystal size 30,96-33,48 nm and by DR-UV resulted Eg = 3.8 eV. ZnO-activated carbon composite produced in gray colour tablet. Based on SEM and BET characterization, composite has a hollow morphology with a surface area of 27.209 m2/g, pore volume of 0.089 cc/g with a radius pores of 3.25 nm and has a high effectiveness in the dye direct blue 3R photodegradation of 95.37%. The optimum pH for photodegradation process is at pH 4 with the effectiveness of 91.92%. The addition of Pb2+ and Cd2+ ions can improve the effectiveness of direct blue 3R photodegradation and can reduce Pb2+ and Cd2+ ions simultaneosly with the optimum concentration of each metal were 12 ppm and 9 ppm. The addition of Pb2+ and Cd2+ ions produce the optimum concentration of 9 ppm and 12 ppm in photodegradation of Direct Blue 3R by 94.70% and 93.70% and can photoreduced Cd2+ and Pb2+ ions by 40.67% and 87.67%. The optimum time for photodegradation process was 4 hours.